2020
DOI: 10.1128/aac.01872-19
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Compassionate Use of Cefiderocol To Treat Chronic Osteomyelitis Caused by Extensively Drug-Resistant Pseudomonas aeruginosa and Extended-Spectrum-β-Lactamase-Producing Klebsiella pneumoniae in a Pediatric Patient

Abstract: We report a 15 year-old Nigerian adolescent male with chronic osteomyelitis caused by an extensively drug-resistant (XDR) Pseudomonas aeruginosa strain of sequence type 773 (ST773) carrying blaNDM-1 and an extended spectrum β-lactamase (ESBL)-producing Klebsiella pneumoniae strain. The patient developed neurological side effects in the form of circumoral paresthesia with polymyxin B and asymptomatic elevation of transaminases with aztreonam (used in combination with ceftazidime-avibactam). Cefiderocol treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(53 citation statements)
references
References 14 publications
0
53
0
Order By: Relevance
“…To our knowledge, this is the first case of PJI due to XDR Enterobacterales successfully treated with cefiderocol monotherapy. Alamarat et al reported a compassionate use of cefiderocol to treat chronic osteomyelitis caused by metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa and an ESBL-producing Klebsiella pneumoniae in a 15-year-old patient [2]. The patient had a successful clinical outcome, with only self-resolved possible hematological toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, this is the first case of PJI due to XDR Enterobacterales successfully treated with cefiderocol monotherapy. Alamarat et al reported a compassionate use of cefiderocol to treat chronic osteomyelitis caused by metallo-β-lactamase (MBL)-producing Pseudomonas aeruginosa and an ESBL-producing Klebsiella pneumoniae in a 15-year-old patient [2]. The patient had a successful clinical outcome, with only self-resolved possible hematological toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Ce derocol has been used for a longer period in some compassionate treatments like osteomyelitis (14 weeks), intra-abdominal (28 days) and endovascular infections (30 days) due to XDR germs. All three patients recovered and no emergence of resistance to ce derocol was reported (10,11,12).…”
Section: Introductionmentioning
confidence: 85%
“…Combination therapy with aztreonam and cefiderocol was originally used, but aztreonam was discontinued after 2 weeks due to increasing liver function markers. Intermittent episodes of decreased white cell count with nadir at 1200/mm 3 was noted on cefiderocol therapy and resolved spontaneously without any adjustments [45].…”
Section: Clinical Efficacymentioning
confidence: 99%